The psychological and social impact of female genital mutilation: A holistic conceptual framework - Jennifer Glover; Helen Liebling; Hazel Barrett; Simon Goodman (Journal of International Studies)
Objectives: The current research aimed to gain an understanding of women’s experiences of FGM to develop an evidence based holistic conceptual framework for professionals dealing with the impact of FGM and responses required for survivors and their children. Method: Using a grounded theory approach, qualitative semi-structured interviews were carried out with 20 women survivors of FGM. Results: Participant’s related culture, religion, role of men, lack of education, female identity and deception as the major factors influencing their understanding and the impact of FGM. Their experiences of FGM, as well as being influenced by their conceptualisation of the practice, led to effects on their emotional life, relationships, identity, and physical body. The fear resulting from FGM that women described affected their ability to enhance their resilience. All the core categories of emotional, relational, identity, and physical impact, as well as resilience, were further influenced by the key stages of womanhood; including menstruation, marriage and childbirth. Women voiced their views that all the above issues were compounded by their needs not being met and the lack of meaningful and effective service responses. Conclusions: There are complex systems and relationships that influence the psychological and social impact of FGM. These have core implications for clinical and policy in relation to maternity and healthcare services.